Problems Facing Muslim Consumers of Imported Cosmetic Products Not Labeled as Halal (Study of Law No. 33 of 2014 Concerning Halal Product Guarantees) - Fitri Rafianti (Yayasan Multidimensi Kreatif, 2025)
In recent decades, Muslim awareness of the importance of halal products has increased, not only in food and beverages but also in other sectors such as pharmaceuticals and cosmetics. The halal cosmetics industry has experienced significant growth in recent years, opening up opportunities for the import of cosmetics in Indonesia, both offline and online. However, this has not been accompanied by binding regulations for either producers or distributors, leading to various problems. Among these is the frequent inclusion of halal labels on packaging that contain non-halal ingredients, particularly in cosmetics containing mercury and other hazardous substances. In other practices, many imported cosmetics are still found to be circulating without halal labels, This has caused uncertainty among Muslim consumers and opened the door to legal issues, consumer protection concerns, and questions about the effectiveness of regulations regarding the entry of foreign products with halal labels. Therefore, several important issues need to be discussed, namely: How do regulations govern the circulation of imported cosmetic products, and how does Law No. 33 of 2014 on Halal Product Guarantees regulate halal labels for cosmetics? Additionally, what are the challenges faced by Muslim consumers regarding imported cosmetics without halal labels, The research method used in this study is the normative juridical method, whereby the researcher conducts an assessment based on laws, government regulations, and other legal sources as a basis for analyzing the issue. The distribution of imported cosmetics in Indonesia related to Halal Product Guarantee shows challenges, especially in terms of harmonizing halal labeling requirements between institutions. Uncertainty in implementation at the business level causes ambiguity in the application of regulations. Law No. 33 of 2014 concerning halal product guarantee is expected to provide clarity for producers whose products are distributed in the domestic market.